Korelasi Kadar Serum VEGF-A dengan Rasio Albumin-Kreatinin Urin pada Pasien Penyakit Ginjal Diabetik - Syaiful, Hannie Q; Priyono, Drajad; Harun, Harnavi; Murni, Arina W; Hanif, Akmal M; Faheri, Eifel; Arnelis, Arnelis; Yoga, Vesri (UI Scholars Hub, 2025)
Introduction. Diabetic kidney disease (DKD) is a major microvascular complication of diabetes mellitus, characterized by persistent albuminuria and a progressive decline in glomerular filtration rate (GFR), making it a leading cause of chronic kidney disease (CKD) and end-stage renal disease. Vascular endothelial growth factor-A (VEGF-A) is implicated in the pathogenesis of DKD, being overexpressed in the kidneys and contributing to increased vascular permeability, inflammation, and fibrosis. Albuminuria, an early indicator of renal damage in DKD, is a strong predictor of CKD progression and cardiovascular events. The urine albumin-to-creatinine ratio (UACR) is the recommended test for detecting and monitoring albuminuria. This study aimed to investigate the correlation between serum VEGF-A levels and UACR in patients with DKD. Methods. This cross-sectional analytical observational study involving DKD patients at the Outpatient Clinic of Dr. M. Djamil General Hospital Padang from May to October 2024. Demographic and clinical data were collected. Blood samples were taken for serum VEGF-A measurement using ELISA, and morning spot urine samples were collected for UACR measurement using immunoturbidimetry. Correlation analysis was performed using the Spearman test. Ethical approval was obtained from the Health Research Ethics Committee of Dr. M. Djamil General Hospital Padang. Results. A total of 30 PGD patients were included in the study. The mean age was 61.9 years (SD 9.75), and 53.3% of the participants were male.The mean serum VEGF-A level in DKD patients was 131.34 (SD 83.9) pg/ml, and the mean UACR was 403.90 (SD 53.1) mg/g creatinine. There was a very strong positive correlation between serum VEGF-A levels and UACR (r = 0.993, p < 0.05). Conclusions. Serum VEGF-A levels are very strongly and positively correlated with UACR in DKD patients. Serum VEGF-A may serve as a potential marker for assessing DKD progression and risk of complications, as well as a potential therapeutic target.